Stakeholder Analysis of Implementation of Social Forestry Program at KPH Telawa, Central Java - Baharinawati Wilhan Hastanti; S. Agung Sri Raharjo (Jurnal Wasian, 2021)
Social Forestry at Java island or known as IPHPS (Permit for the Utilization of Social Forestry) is part of the agrarian reform of the forestry sector which expected to solve tenurial problems and improve forest governance. The successful implementation of this program could not be separated of the roles of stakeholder involved. This study aimed to 1) identified stakeholders and their roles in the implementation of IPHPS, and 2) analyzed the relationships between stakeholders in the implementation of IPHPS. This research was conducted in the KPH Telawa area of Boyolali Regency, Central Java. This research uses a combination of qualitative and quantitative approaches. Data collection was done by observation, interviews, and literature studies. Data were analyzed based on the research objectives at stakeholder analysis conducted by identifying stakeholders and their roles as well as the relationships between them in the implementation of IPHPS. They involved in the implementation of IPHPS at the Telawa KPH included Perhutani (KPH) Telawa, KTH IPHPS holders (Wonomakmur 1, Wonomakmur 2, Wonolestari 1, and Wonolestari 2) LMDH Participants PHBM, BPKH IX, BPDASHL Pemali Jratun, Field Companion, BDK Kadipaten, Forestry Foundation, NGO Rejo Semut Ireng, PSKL, LHK Office of Central Java Province, BPSKL Jabalnusra, Forest Development Financing Center Public Service Agency (P3H-BLU). Each of the above stakeholders has their respective strengths and interests. This affects the pattern of relations between the stakeholders which in turn will determine the results of the program. A good relationship will support the successful implementation of the program while a bad relationship can hamper the implementation of the program.Keywords: analysis, stakeholders, implementation, social forestry